Statin reduces mortality and morbidity in systemic lupus erythematosus patients with hyperlipidemia: A nationwide population-based cohort study. Issue 1 (November 2015) - Yu, Hsin-Hui; Chen, Pau-Chung; Yang, Yao-Hsu; Wang, Li-Chieh; Lee, Jyh-Hong; Lin, Yu-Tsan; Chiang, Bor-Luen
Abstract: Objective: The anti-inflammatory and cardiovascular protective effects of statin for patients with systemic lupus erythematosus (SLE) are not clear. We tested the hypothesis that statin use is associated with reduced mortality and morbidity in SLE patients with hyperlipidemia. Methods: We included 4095 patients with SLE and hyperlipidemia from the entire population using the Taiwan National Health Insurance Research Database between 1997 and 2008. A total of 935 matching sets (1:2) of patients who had never used lipid-lowering medications and statin users were included in the nested matched cohort. Cox proportional hazards regression was used to calculate the hazard ratios (HR) and 95% confidence intervals (CI) for the association between statin and all-cause mortality, coronary artery disease (CAD), cerebrovascular disease (CVD) and end-stage renal disease (ESRD), conditional for matching sets in the matched cohort. Results: The multivariate adjusted hazard ratios (HR) for statin users, as compared with patients had never used lipid-lowering medications, were 0.67 (95% CI, 0.54 to 0.83) for death from any cause. High-dose statins (>365 cumulative defined daily dose) significantly reduced risk of all-cause mortality (HR 0.44, 95% CI 0.32 to 0.60); CAD (HR 0.20, 95% CI 0.13 to 0.31); CVD (HR 0.14, 95% CI 0.08 to 0.25); and ESRD (HR 0.22, 95% CI, 0.16 to 0.29), with similar results in the nested matched study. Conclusion: Statin therapy in SLE patients with hyperlipidemia may reduce the risk of mortality, cardiovascular disease and ESRD. The effect of statins needs to be demonstrated in large prospective studies with long-term follow-up. Highlights: Statins exhibit anti-hyperlipidemic, anti-inflammatory and immunomodulating properties. The associations between statin and mortality/morbidity were analyzed using Cox regression in a nationwide cohort of SLE. Statin reduced mortality and morbidity among SLE patients with hyperlipidemia in a dose–response relationship.